Single Cell Reactomics: Real‐Time Single‐Cell Activation Kinetics of Optically Trapped Macrophages. Issue 4 (11th February 2021) - Vasse, Gwenda F.; Buzón, Pedro; Melgert, Barbro N.; Roos, Wouter H.; van Rijn, Patrick
Abstract: Macrophages are well known for their role in immune responses and tissue homeostasis. They can polarize towards various phenotypes in response to biophysical and biochemical stimuli. However, little is known about the early kinetics of macrophage polarization in response to single biophysical or biochemical stimuli. Our approach, combining optical tweezers, confocal fluorescence microscopy, and microfluidics, allows us to isolate single macrophages and follow their immediate responses to a biochemical stimulus in real‐time. This strategy enables live‐cell imaging at high spatiotemporal resolution and omits surface adhesion and cell–cell contact as biophysical stimuli. The approach is validated by successfully following the early phase of an oxidative stress response of macrophages upon phorbol 12‐myristate 13‐acetate (PMA) stimulation, allowing detailed analysis of the initial macrophage response upon a single biochemical stimulus within seconds after its application, thereby eliminating delay times introduced by other techniques during the stimulation procedure. Hence, an unprecedented view of the early kinetics of macrophage polarization is provided. Abstract : Knowledge on the early kinetics of macrophage responses to single biophysical or biochemical stimuli is limited. Here, an optical tweezer‐based method is developed to study macrophage responses to single stimuli with high spatiotemporal resolution and in real‐time on a single‐cell level. Implementation of this technique in macrophage polarization research will gain novel insights into the mechanisms involved in macrophage activation.